Communicative Texts' Modelling of Engineering Profiles as a Methodological Problem; Procedia - Social and Behavioral Sciences; Vol. 215 : International Education and Cross-Cultural Communication, Problems and Solutions, (IECC 2015) - Kurikova N. V. Nataljya Vladimirovna; Medvedeva L. G. Larisa; Nadezhdina E. Yu. Elena Yurjevna; Ruchina A. V. Aleksandra Viktorovna (2015, 2015)
Title screen